1999
DOI: 10.1021/jm990241l
|View full text |Cite
|
Sign up to set email alerts
|

Ecteinascidin 743:  A Minor Groove Alkylator That Bends DNA toward the Major Groove

Abstract: The ecteinascidins (Ets), which are natural products derived from marine tunicates, exhibit potent antitumor activity. Of the numerous Ets isolated, Et 743 is presently being evaluated in phase II clinical trials. Et 743 binds in the minor groove of DNA and alkylates N2 of guanine. Although structurally similar to saframycin, which exhibits poor activity in cellular assays, Et 743 has shown good efficacy as an antitumor agent. In this study, DNA structural distortions induced by Et 743 were examined to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
125
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(135 citation statements)
references
References 24 publications
8
125
0
2
Order By: Relevance
“…Exactly how ET-743 could affect interaction with other factors is an open question. However, Hurley and colleagues (11) have shown that ET-743 bends DNA toward the major groove, which is a unique feature among DNA-interactive agents that occupy the minor groove. One could envision how the interaction of ET-743 with DNA could alter local promoter architecture, preventing functional complex formation or inhibiting interactions with other components of the transcriptional machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exactly how ET-743 could affect interaction with other factors is an open question. However, Hurley and colleagues (11) have shown that ET-743 bends DNA toward the major groove, which is a unique feature among DNA-interactive agents that occupy the minor groove. One could envision how the interaction of ET-743 with DNA could alter local promoter architecture, preventing functional complex formation or inhibiting interactions with other components of the transcriptional machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that ET-743 is toxic to most tumor cell lines in the nanomolar to subnanomolar range; indeed, antitumor effects were observed in phase I trials with concentrations of less than 2 mg͞m 2 body weight. Although ET-743 has been shown to bend and alkylate DNA in the minor groove (11,12), cause microtuThis paper was submitted directly (Track II) to the PNAS office.…”
mentioning
confidence: 99%
“…As a result, the minor groove is opened up and bended toward the major groove (19). The direction of bending is a novel feature among DNA minor groove-interactive agents, making ET-743 unique.…”
mentioning
confidence: 99%
“…Esta molécula liga-se à guanina em sequên-cias específicas de bases nas fendas menores da dupla hélice, causando uma dobra nas fitas de DNA. 45,46 Este dobramento tem diversas consequências celulares que são refletidas na desorganização do citoesqueleto, bloqueio da divisão celular e interferência no reconhecimento e ligação normal de fatores de transcrição ou proteínas ligantes ao DNA, causando ativação ou inibição de determinados genes. 47,48 A inibição da transcrição do gene MDR1 é um dos principais e mais relevantes efeitos desta substância, sendo este gene responsável pela produção de glicoproteína-P, uma proteína que realiza o bombeamento de diversos quimioterápicos para fora das células e pode estar superexpressa em células tumorais.…”
Section: Ara-c (Citarabina ® ) E Ara-a(vidarabina ® )unclassified